In nomine Diaboli: The ideologies of organized crime - Poppi, Fabio Indìo Massimo (European journal of criminology, 2023)
This article addresses the topic of ideologies underlying organized crime using interviews with individuals living in Mafia-affected territories. High school and university students produced narratives that reflected their ideologies about organized crime, which were duly compared with the ideologies endorsed by Mafia members in televised interviews. This comparison has yielded several similarities, namely the presence of amoralism, familism, verticalism and religious relativism, but, at the same time, substantial differences in the form of anti-reductionism, anti-normalism and anti-victimism (vis-à-vis reductionism, normalism and victimism). The thrust of this study is that ideologies about organized crime are, to a large extent, shared by members of organized crime and outsiders living in Mafia-affected areas.